Ultrasonographic evaluation of lung parenchyma involvement in sarcoidosis - Doğan, Coşkun; Kıral, Nesrin; Parmaksız, Elif Torun; Çağlayan, Benan; Sağmen, Seda Beyhan; Salepçi, Banu; Fidan, Ali; Cömert, Sevda Şener (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Purpose: To use ultrasonography (USG) for the evaluation of lung parenchyma in patients with sarcoidosis, andto compare the USG findings with the results of a high-resolution computerized tomography (HRCT) and pulmonary function test-carbon monoxide diffusion test (PFT-DLCO), which are commonly used methods in the evaluation of parenchymal involvement in sarcoidosis. Material and Methods: Patients with sarcoidosis and healthy controls were enrolled in the study between January 2015 and December 2017. The clinical findings, HRCT and PFT-DLCO results of all subjects were recorded, and USG findings and comet tail artifact (CTA) measurements were recorded by another pulmonologist. The USG, HRCT and SFT-DLCO findings were compared between the two groups. Based on the findings of theclinical-radiologic investigations and PFT-DLCO, as the current gold standard in diagnosis, the sensitivity and specificity of USG in demonstrating lung parenchyma involvement in sarcoidosis patients were estimated. Findings: The sarcoidosis group consisted of 79 patients and the control group included 34 subjects. The mean number of CTAs in the sarcoidosis and control groups was 33.4 and 25, respectively (p=0.001). In the sarcoidosis group, the number of CTAs in patients with DLCO%